Well‐Defined Segment of Carbon Nanotube with Bright Red Emission for Three‐Photon Fluorescence Cerebrovascular Imaging. Issue 19 (8th July 2021) - Qiu, Zhen‐Lin; He, Mu‐bin; Chu, Ke‐Shan; Tang, Chun; Chen, Xuan‐Wen; Zhu, Liang; Zhang, Li‐Ping; Sun, Di; Qian, Jun; Tan, Yuan‐Zhi
Abstract: As the shortest segment of carbon nanotubes (CNTs), cycloparaphenylenes (CPPs) offer a well‐defined alternative for CNTs as the fluorophores in bioimaging. However, most of CPPs emit blue or yellow light, the bright red‐emitting CPP materials required by bioimaging, particularly in vivo imaging, are still lacking. Here, it is shown that a CPP (TB[9]CPP) with red emission up to 650 nm is successfully synthesized and characterized. The fluorescence quantum yields of TB[9]CPP are measured up to 44% in chloroform and 17% as nanodots in aqueous media. Meanwhile, the water‐soluble nanodots present outstanding three‐photon fluorescence performances, thereby are utilized for in vivo probing of brain vessels by three‐photon fluorescence microscopic imaging technique, exhibiting a high penetration depth, good resolution, and clear image contrast. Abstract : A bright red emissive segment of carbon nanotube TB[9]CPP is realized by a combined strategy of ring‐shrinking and D‐A conjugation. The water‐soluble nanodots of TB[9]CPP with an emission at 650 nm are used for three‐photon fluorescence bioimaging of mouse cerebrovascular, showing high penetration depth, resolution, and image contrast.